Effects of combined radiotherapy with immune checkpoint blockade on immunological memory in luminal-like subtype murine bladder cancer model - JiaMin Huang; Eva Michaud; Surashri Shinde-Jadhav; Sabina Fehric; Gautier Marcq; Jose Joao Mansure; Fabio Cury; Fadi Brimo; Ciriaco A. Piccirillo; Wassim Kassouf (Cancer Biology & Therapy)
MIBC is a highly lethal disease, and the patient survival rate has not improved significantly over the last decades. UPPL is a cell line that can be used to recapitulate the luminal-like molecular subtype of bladder cancer and to discover effective treatments to be translated in patients. Here, we investigate the effects of combinational treatments of radiotherapy and immunotherapy in this recently characterized UPPL tumor-bearing mice. We first characterized the baseline tumor microenvironment and the effect of radiation, anti-PD-L1, and combinatorial treatments. Then, the mice were re-challenged with a second tumor (rechallenged tumor) in the contralateral flank of the first tumor to assess the immunological memory. Radiation slowed down the tumor growth. All treatments also decreased the neutrophil population and increased the T cell population. Anti-PD-L1 therapy was not able to synergize with radiation to further delay tumor growth. Furthermore, none of the treatments were able to generate immune memory. The treatments were not sufficient to induce a significant and lasting pool of memory cells. We show here that anti-PD-L1 treatment added to radiotherapy was not enough to achieve T cell-mediated memory in UPPL tumors. Stronger T cell activation signals may be required to enhance radiation efficacy in luminal-like bladder cancer.